Effectiveness Of Land and Building Tax Collection by Villages in Sukaraja Sub-District - Arsyu, Muhammad Ilham Effendi; Purwanti, Dian; Nur, Tuah (Indonesian Journal Publisher, 2024)
Sukaraja Sub-district is still less effective in carrying out the collection of PBB, this is in accordance with what is conveyed by Duncan who explains that, effectiveness comes from the word effective, namely a job is said to be effective if the job can achieve the goals or objectives that have been determined and can be completed on time in accordance with the plan that has been set. The research method used in this research is qualitative research method, which aims to reveal qualitative information so that it emphasises more on process and meaning issues by describing a problem. The achievement of taxpayer goals is measured by the achievement of tax assessment, the obedience of the community to pay taxes and the timeliness of the community to pay taxes. Both according to the agency and the community, the achievement of taxpayer goals by the Village in Sukaraja Sub-district, Sukabumi District is still less effective. Adaptation in Sukaraja Sub-district is still not effective because adaptation by developing strategies is just in process.